Informal employment, population health, and welfare policies: A global empirical analysis between 2011–2021 - Amanda E. Aronsson; Indra de Soysa (PLoS ONE, 2025)
Despite informal employment being the most common type of employment globally, the empirical link between informality and health is underexplored. Using time-series, cross sectional data from the International Labor Organization (ILO) on informal employment for roughly 126 countries between 2011–2021, this study applies OLS regression to explore how informality associates with population health, measured as healthy life expectancy (HALE), maternal mortality, under-five mortality, equality of access to health care, and mortality due to communicable diseases and maternal and prenatal undernutrition. We also address whether this relationship is conditioned by the availability of higher quality welfare state. The results show that informality associates with a host of measures of poor health, controlling for important confounders, but it associates weakly positively with HALE. Contrary to expectations, an accessible welfare state does not condition informality in ways that lower the health burden. Our results are possibly not causal but subject to endogeneity bias since bad health conditions could lead to increased welfare policies. Longer time series of informal employment data is needed for further assessment. The basic results, however, point to a connection between the size of the informal workforce and diminished population health, controlling for important confounders.